Chitosan-based nanoparticles as drug delivery systems: a review on two decades of research. (21st April 2019) - Naskar, Sweet; Kuotsu, Ketousetuo; Sharma, Suraj
Abstract: Chitosan (CS) is one of the most functional natural biopolymer widely used in the pharmaceutical field due to its biocompatibility and biodegradability. These privileges lead to its application in the synthesis of nanoparticles for the drug during the last two decades. This article gives rise to a general review of the different chitosan nanoparticles (CSNPs) preparation techniques: Ionic gelation, emulsion cross-linking, spray-drying, emulsion-droplet coalescence method, nanoprecipitation, reverse micellar method, desolvation method, modified ionic gelation with radial polymerisation and emulsion solvent diffusion, from the point of view of the methodological and mechanistic aspects involved. The physicochemical behaviour of CSNPs including drug loading, drug release, particles size, zeta potential and stability are briefly discussed. This review also directs to bring an outline of the major applications of CSNPs in drug delivery according to drug and route of administration. Finally, derivatives of CSNPs and CS nano-complexes are also discussed.